2010
DOI: 10.3109/00016489.2010.528792
|View full text |Cite
|
Sign up to set email alerts
|

CD44 expression is related to poor prognosis of hypopharyngeal squamous cell carcinoma

Abstract: The CD44 expression in hypopharyngeal SCCs was related to pathological N stage, but not to clinical T and N stages and pathological T stage, of the patients. Distant metastasis during the follow-up occurred more frequently in patients with CD44-high SCCs than those with CD44-low SCCs. The 5-year DFS was significantly lower in the former than in the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…Although some studies in human H&N and other malignancies have shown that CD44 can be prognostic for treatment outcome, we did not find a significant correlation between CD44 levels and either ST or PFI in feline oral SCC . One plausible explanation for this discrepancy could be the varied assortment of CD44 isoforms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although some studies in human H&N and other malignancies have shown that CD44 can be prognostic for treatment outcome, we did not find a significant correlation between CD44 levels and either ST or PFI in feline oral SCC . One plausible explanation for this discrepancy could be the varied assortment of CD44 isoforms.…”
Section: Discussioncontrasting
confidence: 99%
“…In human H&N SCC, cancer cells positive for the cell surface marker CD44 (a hyaluronic acid receptor), have been shown to be more tumourigenic than cancer cells negative for CD44 . Other studies revealed that human H&N SCC patients with greater numbers of CD44 positive cancer cells present with more advanced clinical tumour stages and significantly lower survival rates, as well as higher rates of tumour recurrence and tumour implantation in immunocompromised mice . The original study advocating CD44 as a TIC marker, also showed that CD44 positive cancer cells – but not CD44 negative cancer cells – differentially expressed Bmi‐1 at both the RNA and protein levels .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to absent/weak CD44 intensity staining, medium/high CD44 intensity staining correlated to worse prognosis for OSCC in general and for HPV DNA + OSCC. These results are in line with previous reports in HNSCC and other malignancies . Furthermore, it was proposed that CD44 characterize cancer stem cells in HNSCC .…”
Section: Discussionsupporting
confidence: 93%
“…CD44 is a cell-surface glycoprotein involved in cell-cell interactions, cell migration, and adhesion with multiple isoforms (splice variants) known to be associated with cell transformation and tumor dissemination [103106]; Clinically, overexpression of CD44 was associated with poor prognoses and decreased 5-year survival in HNSCC patients [107–110], although its clinical relevance seems dependent on the anatomical site where the cancer originates [106, 111114]. The aldehyde dehydrogenase (ALDH) family of cytosolic enzymes catalyses the oxidation of aliphatic and aromatic aldehydes to carboxylic acids and ALDH1 is a family member that has a role in the conversion of retinol to retinoic acid, which is important for proliferation, differentiation and survival.…”
Section: Clinical Relevance Of Cancer Stem Cells In Oral Tumorigenesismentioning
confidence: 99%